PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN APLIKASI CANVA PADA SUBTEMA KEANEKARAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU - Reza Fara Nuraziza; Lina Novita; Nurlinda Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Developed animated video media using the Canva application on the sub-theme of ethnic and religious diversity in my country. Animated video learning media is a tool used by teachers to convey information in the form of image objects combined with audio to attract students' attention and make situations more effective during the teaching and learning process to achieve learning objectives. Therefore, it is necessary to develop learning media. This research aims to develop animated video media using the Canva application on the sub-theme of ethnic and religious diversity in my country. The research method used is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was carried out at SDN Harjasari 01 Bogor, then the animated video media was validated by media experts, language experts, and material experts and implemented on a limited basis with 27 class IV students. The research results show that animated video media using the developed Canva application is a very feasible category. This is based on the percentage of media experts at 90%, language experts at 100%, material experts at 98%, and student responses with an average gain of 90.4%. Based on the results of this research, it can be concluded that the digital comic learning media developed is very suitable for use as learning media in the classroom.